Decreased endemic malaria in Suriname: moving towards elimination - Edward D. van Eer (Malaria Journal, 2018)
Abstract Background Suriname has moved from being the country with the highest annual parasite index in the Americas to one on the threshold of elimination. The progress toward elimination in the stable populations of Suriname between 2000 and 2015 is reviewed. Methods Data was obtained from the Medical Mission and the Ministry of Health Malaria Programme case-reporting systems, and analysed with a focus on disease burden and differentiation of the disease geographically, by malaria species, age, gender, ethnicity, incidence and gametocytaemia. Results Between 2000 and 2015 there were 57,811 locally acquired cases of malaria in the stable populations of Suriname. A significant reduction in indigenous malaria cases was observed from 2006 to 2015. The number of imported malaria cases saw a relative increase compared to the number of autochthonous cases. In 2015 over 95% of the cases reported in stable communities are imported, mainly from neighbouring French Guiana, a department of France. The overall decline in malaria case incidence followed the mass-distribution of free long-lasting insecticide-impregnated mosquito nets and increased awareness building efforts, improved access to malaria services as a result of the introduction of Rapid Diagnostic Tests and the implementation of active case detection in high risk areas. In addition, improved management of Plasmodium falciparum infections was achieved with the introduction of artemisinin combination therapy. Conclusions The existence of a network of policlinics in the interior ran by Medical Mission, for the indigenous population, allowed the rapid implementation of the strategy in stable communities. The success of malaria control in Suriname indicates that the availability at local level, of prompt and adequate prevention, diagnosis and treatment is a key requirement for the elimination of malaria.